(untitled) (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Problem: The ability to write a short essay among students is low, with an average value of 58.25. This is caused by: (a) students being less able to prepare a well-structured outline; (b) students facing disadvantages in elaborating the outline into a complete and coherent essay; (c) fewer students reading essays with correct punctuation; (d) students being less able to respond to the reading essay correctly. Objective: Based on this problem, researchers want to conduct classroom action research (PTK) with the aim of increasing the ability to write a short essay through the implementation of directed paraphrase strategies. Setting and Subjects: This study was conducted in SD Negeri 014 Silikuan Hulu, Kecamatan Ukui. The subjects were students of class IV with a number of 30 students with details of 15 male students and 15 female students. Methodology: This study was done in 2 cycles, each cycle consisting of two meetings with one daily test. The data collection technique used is the technique of observation activities of teachers and students and the testing techniques brief essay writing skills. The analysis technique used is the analysis of the activity of teachers and students and the results of tests the ability to write a short essay. Results: The results of this study show that implementation of paraphrase strategies directed to improve the ability to write concise essays among Elementary School fourth-grade students in Silikuan Hulu, Kecamatan Ukui. This is confirmed by the data obtained in the research which states that: (a) the activities of teachers has increased in each cycle, meeting one gained 41.66% (category quite perfect), meeting 2 gained 58% (category quite perfect), meetings 3 gained 75% (perfect category), and meeting 4 will acquire 83% (category is perfect); (b) the activity of students has increased at each cycle, meeting one gained 56% (category quite perfect), meeting 2 gained 76% (perfect category), 3 meeting gained 88% (category is perfect), and 4 meeting gained 98% (category is perfect); (c) the results of learning about the ability to write a short essay of students has increased each cycle, the first cycle gained 66.25 and the second cycle obtain 72.75. Increased mastery learning students in the first cycle of 50% and the second cycle by 80%.